Application and influence factors of capacitive deionization method for removing inorganic contaminated ions. Issue 1 (1st January 2021) - Che, Naiju; Liu, Longfei; Liu, Yanli; Li, Chengliang
ABSTRACT: At present, the situation of water contamination seriously hinders the healthy cycle of natural environment and the development of human society. Capacitive deionization technology is a novel water treatment technology for remediating inorganic-contaminated ions from aqueous medium. This paper briefly introduces the related theory and reviews the current research and application in removing inorganic contaminants (heavy metal ions, anionic contaminants, other inorganic contaminants, etc.) in the aqueous solution. In addition, the influence of electrode materials, device design and environmental factors on capacitive deionization of inorganic contaminants was briefly summarized. In order to provide help for the further development and application of the capacitive deionization technology, the summary and prospect are also part of the article. Graphic abstract: uf0001